1991
DOI: 10.1177/135050769102200110
|View full text |Cite
|
Sign up to set email alerts
|

Natural Learning in Committee B

Abstract: INTRODUCTIONThis article focuses on the ability of managers to handle financial management information. Because financial management information has become increasingly important to public sector organisations, the article reports a study conducted with a top management Committee of a Regional Health Authority.The study set out to ascertain if the managers in this Committee had the ability to handle the financial management information with which they were provided, and if this ability changed over time, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
2
6
0
Order By: Relevance
“…These are deliberately brief because full details can be found in each publication. The study with managers in the Regional Health Authority used conversations and personal construct grids in relation to the accounting data received and used (Purdy, 1991a). The study with Ward Unit Managers was with open conversations about the accounting data received and used (Purdy, 1993a).…”
Section: The Methodologies Used and To Be Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…These are deliberately brief because full details can be found in each publication. The study with managers in the Regional Health Authority used conversations and personal construct grids in relation to the accounting data received and used (Purdy, 1991a). The study with Ward Unit Managers was with open conversations about the accounting data received and used (Purdy, 1993a).…”
Section: The Methodologies Used and To Be Usedmentioning
confidence: 99%
“…It was conducted with managers in a UK Regional Health Authority and showed that the managers varied in their ability to understand the accounting data provided. The ability to understand might have affected their ability to handle the data and might have altered with training but did alter with learning on the job (Purdy, 1991a).…”
Section: Applications Of Personal Constructionmentioning
confidence: 99%
“…The study found that each member of the committee indicated different abilities to construe financial management accounting data. Those who had been trained, even on the job, indicated more ( ) financial management accounting constructs Purdy, 1991b . With the second study, the managers of ward units in a teaching hospital received data relating to their own unit in the same format.…”
Section: The Users Of Management Reportsmentioning
confidence: 99%
“…What accounting data do Ward Unit Managers provide to their Ward Sisters; how do the Ward Sisters view this; and does natural learning occur? Natural learning in this context being the facility of individuals to learn on the job and discover something about financial management accounting (Purdy, 1991).…”
Section: Introductionmentioning
confidence: 99%